THE CONCEPT OF HAPPINESS IN GIVING ALMS ACCORDING TO THE QUR'AN FROM A RELIGIOUS PSYCHOLOGY PERSPECTIVE - Khotimah, Khusnul (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2024)
The path to achieving happiness in life of each individual has its own uniqueness and way. Many feel happy but there is still a sense of anxiety in their hearts, happy simply because the happiness they get is not the ultimate happiness. In Islam, the real happiness is the happiness of ma'rifatullah. One way to get it is to give alms to others in need. Happiness is achieved by abstinence from various physical pleasures. Those who have attained a high level of holiness are the ones who obtain good fortune and happiness. The research used in this study is a type of literature study research with a qualitative descriptive analysis approach. The data sources used in this study are secondary data sources. The result of this research is that to achieve true happiness, humans can establish a good relationship with the Creator, one of which is by giving alms with the intention of lillah (because of Allah) not because they want to be seen or known by others. According to religious psychology, happiness can be achieved by getting closer to Allah such as self-muhasabah, gratitude, and almsgiving.